Protection of the Fulfillment of Transgender Rights that Has Permanent Legal Force - Jalaludin, Muhamad; Kusumah, Haidan Angga (Dinasti Research, 2025)
This study examines legal protection for the fulfillment of transgender rights that have obtained permanent legal status in Indonesia. The phenomenon of transgender individuals, as part of global social dynamics, faces complex challenges in legal recognition and human rights protection. With an estimated transgender population of 43,100 people in Indonesia, they continue to experience systematic discrimination in various aspects of life. This research employs a normative-empirical method to analyze the legal aspects that support transgender protection as well as the challenges in its implementation. The findings reveal that although there is a legal basis in the 1945 Constitution and Law No. 39/1999 on Human Rights, as well as court decisions such as the Rohmah case in Cibadak District Court, the implementation of legal protection still encounters structural obstacles in the form of social discrimination and the absence of specific regulations. This study provides recommendations for strengthening a more inclusive and comprehensive legal framework to protect the rights of transgender individuals in Indonesia.